"Bath Salts" the New York City Medical Examiner Experience: A 3‐Year Retrospective Review. Issue 3 (6th December 2016) - deRoux, Stephen J.; Dunn, William A.
Abstract: "Bath salts" are synthetic derivatives of cathinones, compounds found in the leaves of Catha edulis, which possesses amphetamine‐like properties. At the New York City Office of Chief Medical Examiner, we conducted a 3‐year retrospective analysis of deaths in which cathinones were detected. Two categories emerged; those in which cathinones were a contributory cause of death (15 cases) and those in which they were an incidental finding (15 cases). Of the former group, 13 were associated with additional intoxicants; two deaths were attributed solely to cathinone intoxication, both survived 10 h: a man whose postmortem blood methylone concentration was 0.71 mg/L and a woman whose postmortem blood ethylone concentration was 1.7 mg/L. In the latter category, there were several individuals who had higher concentrations of cathinones than the above two, the highest being a blood methylone of 4.8 mg/L. Based upon our data and the literature presented, lethal concentrations of cathinones cannot be established.